2009
DOI: 10.1039/b816853a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in enantioselective copper-catalyzed 1,4-addition

Abstract: A comprehensive overview of recent literature from 2003 concerning advances in enantioselective copper catalysed 1,4-addition of organometallic reagents to alpha,beta-unsaturated compounds is given in this critical review. About 200 ligands and catalysts are presented, with a focus on stereoselectivities, catalyst loading, ligand structure and substrate scope. A major part is devoted to trapping and tandem reactions and a variety of recent synthetic applications are used to illustrate the practicality and curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(122 citation statements)
references
References 234 publications
(175 reference statements)
0
119
0
3
Order By: Relevance
“…[146,147] [111][112][113] Zu diesen Liganden gehören Derivate von Octahydro-BINOL L3, [150] TADDOLen L4, [137,151] 8,8'-verknüpften Binaphtholen L9 [152] und Spirobiindandiolen L11, [153,154] die Phosphoramidite von Zuckerphosphiten L12 [155] und 9,9'-Spirobixanthenderivate L10 [156] (Abbildung 2). Allerdings erreichten nur wenige dieser neu entwickelten Liganden in der Cu-katalysierten konjugierten Addition von Dialkylzinkreagentien an Enone die Ausbeuten und Enantioselektivitäten, die mit den früher beschriebenen Phosphoramiditen [31,32,63,112,127] (siehe Abbil- Auch die flexiblen Biphenol-Phosphoramidite L16 (siehe Abbildung 5) mit sterisch anspruchsvollen Substituenten an der Aminogruppe wurden als Liganden in der konjugierten Addition an Nitroalkene untersucht. [164] In einer ähnlichen Arbeit wurden Derivate des Biphenol-Liganden L16 mit verschiedenen Substituenten an der Biphenoleinheit eingesetzt.…”
Section: Abfangen Von Reaktionszwischenstufen Mit Elektrophilenunclassified
“…[146,147] [111][112][113] Zu diesen Liganden gehören Derivate von Octahydro-BINOL L3, [150] TADDOLen L4, [137,151] 8,8'-verknüpften Binaphtholen L9 [152] und Spirobiindandiolen L11, [153,154] die Phosphoramidite von Zuckerphosphiten L12 [155] und 9,9'-Spirobixanthenderivate L10 [156] (Abbildung 2). Allerdings erreichten nur wenige dieser neu entwickelten Liganden in der Cu-katalysierten konjugierten Addition von Dialkylzinkreagentien an Enone die Ausbeuten und Enantioselektivitäten, die mit den früher beschriebenen Phosphoramiditen [31,32,63,112,127] (siehe Abbil- Auch die flexiblen Biphenol-Phosphoramidite L16 (siehe Abbildung 5) mit sterisch anspruchsvollen Substituenten an der Aminogruppe wurden als Liganden in der konjugierten Addition an Nitroalkene untersucht. [164] In einer ähnlichen Arbeit wurden Derivate des Biphenol-Liganden L16 mit verschiedenen Substituenten an der Biphenoleinheit eingesetzt.…”
Section: Abfangen Von Reaktionszwischenstufen Mit Elektrophilenunclassified
“…[6] However, the relationship of the stoichiometric lithium cuprate chemistry presented in Scheme 1 to that of the catalytic Cu I /ZnMe 2 /L* systems (M = ZnMe, L* = a phosphoramidite ligand) has remained somewhat obscure. Kinetic studies of chiral copper(I)-phosphoramiditecatalyzed additions of ZnR 2 to enones are limited to early observation of a negative non-linear effect [7] and a recent study of the effect of the ligand structure on the rate by Schrader et al [8] Additional information on potential interaction modes between the CuX precatalyst and the chiral ligand were gained from comprehensive NMR studies of Gschwind et al [9] As the cuprate intermediates in Cu I /ZnMe 2 /L*-promoted reactions are very labile, we sought to harness the power of DFT-based calculations [10] to gain insight into the potential structures of p-complex C (M = MeZn, L* = phosphoramidite) in this zinc chemistry and their subsequent redox behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Several aspects concerning these ligands are still unclear, though. Interestingly, a number of investigations have shown that P* ligands do not always act as monodentate.…”
Section: Introductionmentioning
confidence: 99%